1997
DOI: 10.1046/j.1365-2133.1997.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Olmsted syndrome: report of a new case

Abstract: We report the case of a 20-year-old man, who was born with an intense erythema of the genital area, unresponsive to any treatment employed. When he was 9 months old, he presented with well-defined hyperkeratotic erythematous plaques around the mouth, eyes, nose, and perianal area, with similar plaques on the lateral aspect of the neck and axillae. At the same time the erythema of the genital area became hyperkeratotic. When he was 2 years old, he presented with a disabling palmoplantar keratoderma, initially f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…1 These two features are the hallmarks for the diagnosis of this condition. 2 Other features associated with the syndrome were described subsequently by various other authors, and new associated features continue to be reported. Nevertheless, it remains a rarely reported entity.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…1 These two features are the hallmarks for the diagnosis of this condition. 2 Other features associated with the syndrome were described subsequently by various other authors, and new associated features continue to be reported. Nevertheless, it remains a rarely reported entity.…”
Section: Introductionmentioning
confidence: 74%
“…Although new cases have increased the number of cutaneous and systemic features that may be seen in this disease, it is widely accepted that the two major findings that are prerequisites for diagnosis are the symmetrical involvement of the palms and soles with keratoderma, and symmetrical hyperkeratotic plaques in the periorificial areas. 2 The syndrome seems to be of sporadic occurrence, 4 although a familial case with a possible autosomal dominant transmission 5 and another case with X-linked dominant transmission in two monozygotic male twins 6 have been reported. The pathogenesis of this disorder is poorly understood but it is now believed to be a disorder of keratinization, and Kress et al found a defect in the expression of mature epidermal keratins (types 1 and 10) and persistence of acidic keratins (types 5 and 14) in the involved epidermis.…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The two major ones are the symmetrical involvement of keratoderma of the palms and soles and the symmetrical hyperkeratotic plaques around the body orifices. It starts in the neonatal period or in childhood [25]. The disease has a slow but progressive and extremely disabling course [1, 3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, perianal and inguinal plaques frequently show maceration and infection by bacteria and Candida albicans [4]. The differential diagnosis includes other syndromes of palmoplantar keratoderma and hyperkeratotic syndromes [25]. …”
Section: Discussionmentioning
confidence: 99%